Immature stages and host plant records for the skipper butterflies Xeniades orchamus (Cramer, 1777), Dubia dubia (Bell, 1932), and Tricrista canta (Evans, 1955) in the Peruvian Amazon (Lepidoptera: Hesperiidae: Hesperiinae: Hesperiini) - Sherer, A.; Raghuraman, S.; Nakahara, S.; Gallice, G. (Magnolia Press, 2025)
We describe the immature biology of three skipper species in the tribe Hesperiini (Hesperiidae: Hesperiinae), Xeniades orchamus Cramer in the subtribe Hesperiina, and Dubia dubia Bell and Tricrista canta Evans in the subtribe Moncina. All species were recorded feeding on Guadua weberbaueri Pilger (Poaceae: Bambusoideae: Bambuseae). One larva of each species was collected in nature at Finca Las Piedras, a biological research station located in the Amazonian lowlands of Madre de Dios, Peru. Larvae were reared to adulthood in an onsite laboratory using leaves from G. weberbaueri. We present measurements, descriptions, durations, and photographs of recorded larval instars and pupae, illustrations of larval head capsules, and details of the host plant.
Keywords: Biology; Lepidoptera genitalia; Instar; Larva; Pupa; Host (biology); Amazon rainforest; Botany; Zoology; Ecology; https://purl.org/pe-repo/ocde/ford#1.06.13